Diversity-Oriented Approach for Chemical Biology - Lee, Jun-Seok; Lee, Jae Wook; Kang, Namyoung; Ha, Hyung-Ho; Chang, Young-Tae (WILEY-V C H VERLAG GMBH, 2015)
Synthetic molecules that modulate and probe biological events are critical tools in chemical biology. Utilizing combinatorial and diversity-oriented synthetic strategies, access to large numbers of small molecules is becoming more and more feasible, and research groups in this field can take advantage of the power of chemical diversity. Since the majority of early studies were focused on the discovery of compounds that perturb protein functions, diversity-based approaches are often considered as therapeutic lead discovery tactics. However, the diversity-oriented approach can also be applied to advance distinct aims, such as target protein identification, or the development of imaging probes and sensors. This review provides a personal perspective of the chemical-diversity-based approach and how this principle can be adapted to various chemical biology studies.
Keywords: COLORIMETRIC SENSOR ARRAY; FLUORESCENCE LIBRARY APPROACH; HUMAN SERUM-ALBUMIN; DYNAMIC COMBINATORIAL LIBRARIES; IMAGING PROBE DEVELOPMENT; PLURIPOTENT STEM-CELLS; SOLID-PHASE SYNTHESIS; METAL-DYE COMPLEXES; DATE RAPE DRUG; TRIAZINE LIBRARY